Outcome of patients with distinct molecular genotypes and cytogenetically normal AML after allogeneic transplantation - Schmid, Christoph; Labopin, Myriam; Socié, Gerard; Daguindau, Etienne; Volin, Liisa; Huynh, Anne; Bourhis, Jean Henri; Milpied, Noel; Cornelissen, Jan; Chevallier, Patrice; Maertens, Johan; Jindra, Pavel; et al. (Blood, 2015)
To analyze the influence of distinct combinations of molecular aberrations on outcome after allogeneic hematopoietic stem cell transplantation (HSCT) for cytogenetically normal acute myeloid leukemia (CN-AML), a retrospective registry analysis was performed on 702 adults undergoing HSCT in first complete remission (CR). Patients were grouped according to presence or absence of NPM1 mutations (NPM1(mut)) and FLT3 internal tandem duplications (FLT3-ITD). Double-negative patients were evaluated for mutations of the CCAAT/enhancer binding protein α gene (CEBPα). The influence of genotypes on relapse, non-relapse mortality, leukemia-free survival (LFS) and overall survival (OS), and a prognostic classification combining NPM1/FLT3-ITD profile and classical risk factors were calculated. Two-year OS from HSCT was 81 ± 5% in NPM1(mut)/FLT3(wt), 75 ± 3% in NPM1(wt)/FLT3(wt), 66 ± 3% in NPM1(mut)/FLT3-ITD, and 54 ± 7% in NPM1(wt)/FLT3-ITD (P = .003). Analysis of CEBPα among patients with NPM1(wt)/FLT3(wt) revealed excellent results both in patients with CEBPα(mut) and with a triple negative genotype (2-year OS: 100%/77 ± 3%). In a Cox-model of predefined variables, age, FLT3-ITD and >1 course of chemotherapy to reach CR were risk factors associated with inferior outcome, regardless of NPM1 mutational status, variations of transplant protocols, or development of graft-versus-host disease. In a prognostic risk classification, 2-year OS/LFS rates were 88 ± 3%/79 ± 4% without any, 77 ± 2%/73 ± 3% with one, and 53 ± 4%/50 ± 4 with ≥2 risk factors (P = .003/.002).
Keywords: Leukemia, Myeloid, Acute; tandemové repetitivní sekvence; transplantace hematopoetických kmenových buněk; tyrosinkinasa 3 podobná fms; Humans; lidé středního věku; cytogenetické vyšetření; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Female; Tandem Repeat Sequences; dospělí; Genotype; lidé; Nucleophosmin; Transplantation, Homologous; indukce remise; Adult; staging nádorů; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; nemoc štěpu proti hostiteli; Retrospective Studies; nukleofosmin; prognóza; Remission Induction; fms-Like Tyrosine Kinase 3; genotyp; retrospektivní studie; Neoplasm Staging; míra přežití; Cytogenetic Analysis; mužské pohlaví; homologní transplantace; akutní myeloidní leukemie; Prognosis; následné studie; Survival Rate